Preparing for the challenges of the labour market: The overall competence development role of student research activities - Koloszár, László; Mitev, Ariel Zoltán; Takácsné György, Katalin; Wimmer, Ágnes (Vezetéstudomány / Budapest Management Review, 2024)
Developing skills to meet labour market challenges is a crucial requirement for business education. Student research activities and conferences have a seven-decade tradition in Hungarian higher education and effectively support this goal. In this student-centred, experience-based competence development process, students conduct research on selfchosen topics, while teachers act as facilitators. The best papers are presented at National Student Research Conferences (OTDK). This article reviews and analyses this process from the perspective of competence development and student experience. The effectiveness of the method is illustrated through the opinions of students who participated in economics conferences. The findings show that the OTDK serves as a competition, professional conference, and festival. Beside improving professional competences, it is also an effective tool for fostering the development of soft skills, which are becoming more and more crucial in the workforce of the twenty-first century.